Associated factors of cardiac valve calcification and its prognostic effects among patients with chronic kidney disease: a systematic review and meta-analysis - Zhang, Jialing; Pang, Qi; Wang, Shiyuan; Wu, Leiyun; Zhang, Aihua (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiac valve calcification (CVC) is highly prevalent and a risk factor for adverse outcomes in patients with chronic kidney disease (CKD). This meta-analysis aimed to investigate the risk factors for CVC and association between CVC and mortality in CKD patients. Method Three electronic databases including PubMed, Embase, and Web of Science were searched for relevant studies up to November 2022. Hazard ratios (HR), odds ratios (OR), and 95% confidence intervals (CI) were pooled using random-effect meta-analyses. Results 22 studies were included in the meta-analysis. Pooled analyses showed that CKD patients with CVC were relatively older, had a higher body mass index, left atrial dimension, C-reaction protein level, and a declined ejection fraction. Calcium and phosphate metabolism dysfunction, diabetes, coronary heart disease, and duration of dialysis were all predictors for CVC in CKD patients. The presence of CVC (both aortic valve and mitral valve) increased the risk of all-cause and cardiovascular mortality in CKD patients. However, the prognostic value of CVC for mortality was not significant anymore in patients with peritoneal dialysis. Conclusion CKD patients with CVC had a greater risk of all-cause and cardiovascular mortality. Multiple associated factors for development of CVC in CKD patients should be taken into consideration by healthcare professionals to improve prognosis. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier [CRD42022364970].